Determination of Hormones profile and Semen Parameters for Infertility of Men at Al-Husain Hospitals, Thi-Qar City, Iraq and Effect the Age and Type of Diagnosis - Enas Abdul Kareem Jabbar (Journal of Global Pharma Technology, 2018)
Male factor is responsible for the infertility in about 50% of cases. The people’s perception of infertility varies from culture to culture. So this work amid to determine the prevalence and pattern of endocrinological abnormalities and semen parameters in patients investigated for male infertility in our environment, and any associated between semen’s and hormones’ results. This work included 89 infertility men and 11 healthy as control group. Their age was ranged between 20-50 years old. The volume, concentration and movement of seminal fluid patterns were examined. Then patients were divided to four groups: Azospermia, Oligospermia, and Normospermia poor movement. Follicle-stimulating hormone FSH, luteinizing hormone LH, Prolactin, and Testosterone were determined. The endocrinological diagnosis was done. The highest frequency % of cases was normospermia with poor movement and the lowest was azospermia. The mean of patients’ age was about 34.5 years. The frequencies% of infertility was significantly higher within 25-40 age group. The semen volume was significantly lower in Azospermia and Oligospermia groups. The normal shape sperm and the sperm concentration were lower in all patients groups. FSH, LH, and prolactin levels increased in Azospermia and Oligospermea groups compared to normospermia and control groups. The highest frequency of cases with high FSH, LH, and Prolactin was in Azospermea, and lowest in normospermia while the frequency of cases with high testosterone frequency was (0) in Azospermea and only (1) in Oligospermea, and Normospermea. In Azospermia and Oligospermia, the significantly highest endocrinological diagnosis was germinal epithelial failure. This study reported the significance of proper endocrinological work-up in evaluating patients with infertility where appropriate because these cases may be identifiable endocrine disorders that may be correctable, and that in our environment, endocrine dysfunction is common cause of male infertility. It also reported the frequencies of different endocrine abnormalities, some of which can be successfully processed. We conclude that hormonal evaluations should be performed in the assessment of infertility in males in our environment.